Acidogenic fermentation of municipal solid waste and its application to bio-electricity production via microbial fuel cells (MFCs) - TUĞTAŞ KARNABAT, ADİLE EVREN; ÇALLI, BARIŞ (IWA PUBLISHING, 2011)
Acidogenic fermentation of organic municipal solid waste (MSW) and the bio-electricity production potential from its volatile fatty acid (VFA)-rich leachate using an air-cathode microbial fuel cell (MFC) was investigated in this study. The acidogenic fermentation of 2 kg of MSW has been carried out in a 6 L anaerobic leach-bed reactor (LBR) under mesophilic conditions (30 degrees C). Total production of 92 g VFA expressed as chemical oxygen demand (COD) in 3 L leachate mainly containing acetic, propionic, butyric, and valeric acids has been achieved with manual leachate recirculation and without pH control in 74 days of incubation. Leachate collected on day 32 was used as a feed to an air-cathode MFC after being diluted and supplemented with NaCl or NaHCO3. The maximum power density in the diluted leachate was only 5.9 W/m(3), but reached up to 8.6 W/m(3) upon the addition of 7 mmol/L NaCl. Increase in coulombic efficiency from 6 to 22% was also observed as a result of NaCl supplementation. On the other hand, NaHCO3 addition did not improve the power output.
Keywords: air-cathode; fermentation; leach-bed reactor; volatile fatty acids; GENERATION; INHIBITION; LANDFILL; LEACHATE; ENERGY